Topographic Interpretation of Posterior Keratoconus - Moeen Bhatti, Tayyaba Gul Malik, Muhammad Khalil (Pakistan Journal of Ophthalmology, 2018)
We present a case of a sixty years old Asian male who presented to us with gradual decrease in vision of both eyes. Slit lamp examination revealed paracentral thinning with a dome-shaped excavation in the posterior corneal surface in each eye. Other than the early lens changes, rest of the ocular examination was normal. A diagnosis of bilateral Posterior Keratoconus was made. Corneal topography was done to confirm the diagnosis. Findings of the Galilei scan of the patient are discussed in this case report in relation to normal corneas. Key words: Posterior keratoconus, corneal curvature, Galilei scan, Pachymetry, corneal topography.